FORMATION OF DIFFERENTIAL LAND RENT AND DIFFERENTIAL RENTAL INCOME ON SOILS OF UKRAINE - Smaga, Ivan; MYRONCHUK, Katherina (My University, 2022)
The article examines the essence, peculiarities and factors of forming differential land rent and differential rental income, as well as the methodological aspects of their determination on individual soils by economic indicators of growing small-grain crops (without corn) in the current economic conditions of agricultural production in Ukraine. These economic categories are allotted important role of land relations regulation and the effectiveness of agricultural land use assessment. Differential land rent and differential income it is necessary to install market value of agricultural land. The possibility is shown of using the standards of small-grain crops, production costs for their cultivation and the stock-exchange price of grain sales for a specific year as input data in determining the earning yield of arable land. Identified are the parameters and patterns of the formation of differential land rent (I and II) and differential rental income (I and II) for soils of different genetic nature according to yield standards and production costs for growing grain and leguminous crops in case of natural and potential fertility. The paper presents methodological aspects of distinguishing forms of differential land rent (I and II) obtained during the cultivation of crops with applying fertilizers in accordance with current standards. Differential rent income II under the studied conditions is formed only on soils with higher fertility, and differential rent II — on the least fertile soils
Keywords: differential rental income, differential land rent, natural soil fertility, potential soil fertility, standard yield